Evaluasi Implementasi Pengawasan Berbasis Kewilayahan: Studi Kasus KPP Pratama X - Satyanugraha, Muhammad Ridho; Abbas, Yulianti (Owner : Riset dan Jurnal Akuntansi, 2024)
Regional-based supervision is a new policy implemented by the Directorate General of Taxes in 2020 and revised in 2022. This study aims to evaluate factors related to the implementation of regional-based supervision, which are top management support, regulations, regional account representatives, taxpayers, and information systems. The factors are further divided into thirteen indicators. Previous studies on regional-based supervision and/or tax supervision in general mostly focused on the influence of tax supervision activities on taxpayer compliance or tax revenues. This study differs from previous study because it seeks an in-depth understanding of the implementation of supporting factors in regional-based supervision via an in-depth case study. The interviews involved the office head, the supervision section head, regional account representative, tax consultant, and taxpayers. The results of the study indicate a weakness in the implementation of regional-based supervision related to regulation, both in terms of the availability of regulation that regulate interactions among the parties involved and the clarity in the field of taxation. Additionally, the available budget and the number of account representative personnel still need to be improved.